Theoretical and Practical Approaches in Guidance and Counselling : Educational and Life Perspectives - Leli Kurniat Zega; Maria Titik Windarti (International Forum of Researchers and Lecturers, 2024)
Guidance and counselling is an important element in education and individual development. This article discusses the theoretical and practical approaches underlying guidance and counselling, including their theoretical foundations, methods, as well as their application in education. In addition, an analysis of the counselling approach based on John 4:1-42 shows the relevance of spiritual values in forming a holistic approach. The article also highlights the importance of learner character building as one of the main objectives of guidance and counselling services.